2020
DOI: 10.1186/s13662-020-02899-0
|View full text |Cite
|
Sign up to set email alerts
|

Linear conformable differential system and its controllability

Abstract: This article deals with the sequential conformable linear equations. We have focused on the solution techniques of these equations and particularly on the controllability conditions of the time-invariant system. For the controllability conditions and results, we have defined the conformable controllability Gramian matrix, the conformable fundamental matrix, and the conformable controllability matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Recently, the conformable fractional Gauss hypergeometric function and a class of conformable fractional differential equations through that function were treated in [15]. Further interesting ideas on the conformable derivative can be found in the work by [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the conformable fractional Gauss hypergeometric function and a class of conformable fractional differential equations through that function were treated in [15]. Further interesting ideas on the conformable derivative can be found in the work by [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Note that some authors have demonstrated that the conformable derivative is not the same as a fractional order derivative, but it is a first-order derivative multiplied by an additional factor (see for example [23]). Hence, Definition 1 seems to be a natural extension of the conventional order derivative to noninteger order loosing memory effect.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018 Zhao et al [10] introduced a set of Maxwell's equations using the Generalized Conformable Fractional Derivative (GCFD), which obeys the classical properties of the integer-order derivative. Several works have recently appeared on conformal derivatives, e.g., [14][15][16][17][18][19]. Clearly showing that it is a field of great growth, despite its recent creation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, authors in [18] worked on the controllability of a fractional linear timeinvariant neutral dynamical system. Especially, numerous works from the above citations [15,[19][20][21] have described the complete controllability of conformable systems. In particular, Wang et al [19] investigated the controllability of conformable semilinear systems.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Wang et al [19] investigated the controllability of conformable semilinear systems. In addition, authors in [20] described the linear conformable differential system and its controllability.…”
Section: Introductionmentioning
confidence: 99%